51.6k views
0 votes
Use the distributive property to simplify the expression completely 4-(7c-3)

User Firda
by
4.5k points

1 Answer

2 votes

Given expression:


=4\text{ - (7c - 3)}

Using distributive property:


a(\text{ b + c) = a.b + a.c}

Applying the distributive property:


\begin{gathered} =\text{ 4 - 1(7c -3)} \\ =\text{ 4 -1}*7c-1*-3 \\ =\text{ 4 -7c+ 3} \end{gathered}

Collect like terms:


\begin{gathered} =\text{ }4+3\text{ - 7c} \\ =\text{ 7 - 7c} \end{gathered}

The final expression is:


=\text{ 7 -7c}

User QuentinC
by
4.5k points